Polychlorinated biphenyls (PCBs) and polybrominated biphenyl ethers (PBDEs) in environmental samples from Ny-Ålesund and London Island, Svalbard, the Arctic - Zhu, Chaofei; Li, Yingming; Wanga, Pu; Chen, Zhaojing; Ren, Daiwei; Ssebugere, Patrick; Zhang, Qinghua; Jiang, Guibin (Chemosphere, 2015)
Polychlorinated biphenyls (PCBs) and polybrominated biphenyl ethers (PBDEs) were determined in environmental samples collected from Ny-Ålesund and London Island, Svalbard, the Arctic. Total PCB concentrations (P25PCBs) varied from 0.57 to 2.52 ng g 1 dry weight (dw) in soil, 0.30 to 1.16 ng g 1 dw in plants and 0.56 to 0.98 ng g 1 dw in reindeer dung. The non-Aroclor congener of CB-11 was predominant in most samples compared to other congeners, accounting for 16.0 ± 9.8% to theP25PCBs. TheP13PBDEs concentrations were 1.7–416, 36.7–495 and 28.1–104 pg g 1 dw in soil, plants and reindeer dung, respectively. The signature of enantioselective biotransformation was observed in all samples for chiral CB-95, whereas in parts of samples for other chiral PCBs. Bioaccumulation factors (BAFs) in six plant species varied within individual contaminant congeners and plant species, with BAFs less than 1 for PPCBs and higher than 1 forPPBDEs. BAF values decreased with increasing soil concentrations, suggesting that high background levels in soil restricted the accumulation of these contaminants by plants.
Keywords: PCBs; PBDEs; Soil; Plants; Arctic